2013
DOI: 10.1161/strokeaha.113.001009
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Clinical Usefulness of Intracerebral Hemorrhage Grading Scores

Abstract: Background and Purpose-Various grading scores to predict survival after intracerebral hemorrhage (ICH) have been described. We aimed to test the accuracy and clinical usefulness of 3 well-known scores (original ICH score, modified ICH score, and ICH grading scale) in a large unselected cohort of typical ICH patients. Methods-A total of 1364 ICH cases were referred to our center from January 1, 2008, to October 17, 2010 were prospectively recorded, and the first computed tomography brain scan was retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 16 publications
1
56
0
4
Order By: Relevance
“…Table 2 shows the detailed characteristics of the patients with ICH. The median (IQR) time from stroke onset to admission and GCS score on admission were 1.9 (0.8-9.7) h and 12 (7)(8)(9)(10)(11)(12)(13)(14)(15), respectively. Ninety-nine patients (24.8%) were using antithrombotic agents When compared to patients without cancer, patients with cancer had a longer time from stroke onset to admission, a lower prevalence of hypertension and diabetes mellitus, lower hemoglobin levels, and poorer prestroke, 30-day and 90-day mRS scores, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 shows the detailed characteristics of the patients with ICH. The median (IQR) time from stroke onset to admission and GCS score on admission were 1.9 (0.8-9.7) h and 12 (7)(8)(9)(10)(11)(12)(13)(14)(15), respectively. Ninety-nine patients (24.8%) were using antithrombotic agents When compared to patients without cancer, patients with cancer had a longer time from stroke onset to admission, a lower prevalence of hypertension and diabetes mellitus, lower hemoglobin levels, and poorer prestroke, 30-day and 90-day mRS scores, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…neurological symptoms, hematoma volume and location of hemorrhage) were not evaluated [13]. In this study, the relationship between cancer and ICH outcomes was examined using an ordinal logistic regression analysis, and it was revealed that cancer was associated with poorer outcomes following ICH, independent of known prognostic factors [3][4][5][6][7][8][9][10][11][12]. When the analysis was performed using data from individuals with localized cancer, the effects remained significant after assessment using 90-day mRS but not after that using 30-day mRS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One potential explanation is that prognostic indices based on several factors in combination may predict outcome with better accuracy in neuro-critical care than in other areas in medicine (54)(55)(56)(57)(58). For patients with congestive heart failure, obstructive bronchitis, cirrhosis, kidney disease or cancer, it is rarely possible to prognosticate with certainty that a chronically ill subject will not survive an acute episode (59).…”
Section: Caregivers Have Equal Responsibility Towards Both the Dying mentioning
confidence: 99%